AVALIAÇÃO DA POLÍTICA DE COTAS DA UEPG: DESVELANDO O DIREITO À IGUALDADE E À DIFERENÇA - Souza, Andreliza Cristina de (2012)
Today's society has different ways to solve historical problems, and, in the current on text, the discussions of affirmative action policies are targeted by different approaches and perspectives. This research conducts an evaluation of the quota policy of the State University of Ponta Grossa (UEPG) for the period 2007 to 2010. The objective was to verify of the effectiveness of the quota policy regarding favoring the expansion of access to university for black students from public schools and students from public schools. The first chapter included the theoretical foundation of this work, with contributions from Bourdieu (2004,2009, 2010a, 2010b, 2010c, 2010d) and Bourdieu and Passeron (2008) on the theory of symbolic violence and the reproduction of inequalities within the social and education system.Based on studies of Bobbio (2000), Bobbio, Matteucci and Pasquino (2008) and Crahay (2002), the concepts of democracy, equality and social justice were also treated as fundamental elements for the study of the quota policy. To further the understanding of evaluation and evaluation of public policies, the second chapter brings contributions from Dias Sobrinho (2003; 2004), Arretche (2001; 2007), and Belloni, Magallhães and Souza (2001).This chapter also deals with the sociological focus on the evaluation, proposed by Afonso (2007, 2009). The research was a qualitative case study (ANDRE, 2005; YIN, 2005),and the critical approach was adopted as a methodological option for the research. The instruments chosen for the collection of empirical data were interviews and questionnaires.For empirical data, the methodology of the Collective Subject Discourse of Lefèvre and Lefèvre (2005a, 2005b, 2010) was used, which enabled the construction of summarydiscourses,resulted from the reports of subjects in the research. Institutional documents and the empirical data were analyzed in the third chapter and elucidated how the process of implementing the policy was performed. Although the attempted reproduction of inequalities is perceived and confirmed within the institution, the movement to overcome the social and educational inequalities by the views of education exists, as stated by Cury (1995; 2002). The research allows us to affirm that the policy of quota in UEPG is effective in some aspects and can highlight: a) democratization of access to a portion of previously excluded students in university; b) increase the rates of admission and decreased dropout of quota students during the four year duration of the quota policy; c) proof that the admission through the quota policy does not result in low academic performance. In other aspects, the policy deserves attention from its implementers, due to factors such as: a) discrimination on black quota students; b)absence of a monitoring system for the student from different quota types; c) unsatisfactory conditions for the permanence of quota students. The quota policy of UEPG is valid for eight years and this evaluation, performed during its lifetime, confirms the importance of monitoring the implementation of public policies as a necessary instrument for the exercise of democracy.